Systematic Synthesis of ZnO Nanostructures. Issue 11 (23rd January 2013) - Li, Peng; Wang, Dingsheng; Wei, Zhe; Peng, Qing; Li, Yadong
Abstract In this study, we report a simple solution‐phase method to prepare ZnO nanostructures with controllable morphologies. By using oleylamine (OAm) and dodecanol (DDL) as solvents, zinc oxide nanocrystals with tunable sizes and diverse shapes (hexagonal pyramids, bulletlike, and pencil‐like shapes) have been obtained under mild conditions. At the same time, the introduction of presynthesized gold nanocrystals can also lead to the hybrid nanostructures of gold–zinc oxide hexagonal nanopyramids. In addition, the possible formation mechanism of the as‐prepared ZnO nanostructures has been investigated. Notably, the unique optical properties of the ZnO nanostructures with different sizes and shapes have also been discussed. We hope that this strategy will be a general and effective method for fabricating other metal oxide nanocrystals.